2010
DOI: 10.1007/978-3-642-14295-6_37
|View full text |Cite
|
Sign up to set email alerts
|

RATSY – A New Requirements Analysis Tool with Synthesis

Abstract: Abstract. Formal specifications play an increasingly important role in system design-flows. Yet, they are not always easy to deal with. In this paper we present RATSY, a successor of the Requirements Analysis Tool RAT. RATSY extends RAT in several ways. First, it includes a new graphical user interface to specify system properties as simple Büchi word automata. Second, it can help debug incorrect specifications by means of a game-based approach. Third, it allows correct-by-construction synthesis of systems fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 10 publications
0
96
0
Order By: Relevance
“…Details of the LTL specifications for each scenario can be found in the Appendices. Our algoritm is implemented on top of the GR(1) synthesis tool RATSY [2].…”
Section: Resultsmentioning
confidence: 99%
“…Details of the LTL specifications for each scenario can be found in the Appendices. Our algoritm is implemented on top of the GR(1) synthesis tool RATSY [2].…”
Section: Resultsmentioning
confidence: 99%
“…To list a few, D'Ippolito et al [5,6] used GR(1) to deal with fallible domains and non-anomalous eventbased behavior models; Kress-Gazit et al [11] used GR(1) in robotics; Maoz and Ringert showed GR(1) synthesis for speci cation pa erns [13]. Several tools support GR(1) synthesis, including RATSY [2], TuLiP [24], and Slugs [8]. We give an overview of existing approaches to dealing with unrealizable GR(1) speci cations.…”
Section: Related Workmentioning
confidence: 99%
“…However, notable progress on the problem is underway. RATSY [8] checks realizability of the class of Generalized Reactivity(1) (GR(1) [39]) specifications via an interactive game with the specifier. Acacia+ [9] also solves LTL realizability problems encoded as safety games.…”
Section: Specification Qualitymentioning
confidence: 99%